Overexpressing OsPYL/RCAR7 Improves Drought Tolerance of Maize Seedlings by Reducing Stomatal Conductance - Joon Ki Hong; Yeon-Hee Lee; Beom-Gi Kim; Gang Seob Lee; Hee Jeung Jang; Giha Song; Eun Jung Suh; Sang Ryeol Park (Agriculture, 2022)
Drought stress is a serious abiotic factor limiting the quality and yield of maize (Zea mays). To produce maize plants with enhanced drought tolerance, we generated transgenic maize plants overexpressing OsPYL/RCAR7, encoding an abscisic acid receptor. We crossed the selected lines with maize variety B73 and obtained F1 hybrid seeds. Initial screening suggested that the transgenic lines were more drought tolerant than wild-type plants. Analysis using the DroughtSpotter platform indicated that expressing OsPYL/RCAR7 enhanced drought resistance in transgenic maize seedlings by reducing water loss. In addition, the stomatal conductance of the leaf surface was 30% lower in OsPYL/RCAR7-overexpressing plants than in wild-type ones. After drought treatment, OsPYL/RCAR7-overexpressing maize showed a much higher survival rate than the wild type, suggesting that expressing OsPYL/RCAR7 reduced the negative effects of drought exposure on stomatal conductance and enhanced water use efficiency. Furthermore, the expression levels of drought-tolerance–related abscisic acid–signaling genes ABP2 and RAB16A were higher in the transgenic plants than in the wild type. Taken together, our data indicate that the seedlings of transgenic maize expressing the gene OsPYL/RCAR7 showed increased tolerance to drought stress, raising the possibility that stress-related genes from monocotyledonous crops could be used as genetic resources to improve the agricultural traits of maize.